Media image of Ukraine in a projection onto COVID-19: a linguistic view - Pliasun, Olga (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article is devoted to the analysis of linguistic dominants of Ukraine’s media image modeling during the COVID-19 pandemic. The research is conducted within the framework of a new direction of linguistics – media linguistic imageology, that in both Ukrainian and world linguistics is just beginning to develop, which determines the relevance and scientific perspective of the work. The article highlights the connection of media linguistic imageology with such neolinguistic areas as media linguistics, PR-linguistics, psycholinguistics and suggestive linguistics. The basic principles of linguistic analysis of media image texts about Ukraine are determined, the expediency of their division into two groups is argued: 1) image texts in which information is presented in order to form a positive image of Ukraine (meliorative image texts), 2) media publications which de jure are not image texts but they are such de facto, for instance, media texts about events in political, economic, social, medical and other areas that in one way or another affect the formation of a negative state image (pejorative image texts). Thus, in particular, analyzing media publications about COVID-19, the author includes materials on the development of domestic tourism and the positive aspects of distance learning to the image texts of the meliorative type. The special role of the projects "Travel around Ukraine" and "Tourist Magnets of Ukraine" for repairing the national image in media is emphasized. In turn, the author notes that despite numerous problems in the field of education, its image in the Ukrainian media is generally constructed in a positive way. In the discourse of linguistic analysis, the main image-forming markers of meliorative image texts are the use of metaphorical language, epithets, lexemes with emotionally evaluative positive connotation, new phraseology with positive semantics etc. At the same time, the author emphasizes that the pejorative image texts caused by COVID-19 are media publications about problems in medical, economic, social etc. industries. To create an atmosphere of fear, hopelessness and panic in media publications of this type, journalists use amplifying modal particles and paraphrases with negative contextual semantics etc. The author summarizes that today’s media image of Ukraine is quite contradictory. In the author’s belief, in the difficult conditions of a pandemic a mediator should focus on axiological and ethical principles, information hygiene and respect for recipients.